ANALISIS JALUR PENGARUH PELAYANAN FISKUS, SANKSI PAJAK TERHADAP KEPATUHAN DENGAN KESADARAN WAJIB PAJAK SEBAGAI MEDIASI - Reynaldo; Ngadiman; Jap, Yustina Peniyanti (Fakultas Ekonomi Universitas Tarumanagara, 2025)
Taxes are the largest source of revenue for the Indonesian state. For this reason, maximizing tax revenue must be increased through taxpayer compliance. Some of the factors that affect taxpayer compliance are tax authorities, tax sanctions, and taxpayer awareness. The purposes of this study were to analyze the direct effect of tax authorities, tax sanctions, and taxpayer awareness on taxpayer compliance at KPP Pratama Kalideres. Then, the research also aims to determine the indirect effect between tax authorities and tax sanctions on taxpayer compliance through taxpayer awareness. The main theory used in this research is attribution theory. The research method used is quantitative. The research population is all individual taxpayers with independent work who are registered at KPP Pratama Kalideres. Then the research sample was selected using the hair method and resulted in 170 randomly selected samples. Data analysis using SEM PLS. The results of the study stated that tax authorities, tax sanctions, and taxpayer awareness partially had a positive and significant effect on taxpayer compliance. Furthermore, tax authorities and tax sanctions also have an indirect effect on taxpayer compliance through taxpayer awareness.